2000
DOI: 10.1111/j.1469-445x.2000.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin receptor antagonism — a therapeutic option in heart failure and hypertension

Abstract: The precise role of vasopressin in the pathophysiology of cardiovascular disease is controversial, but this peptide hormone is important for several reasons. Firstly, circulating concentrations of vasopressin are elevated in heart failure and some forms of hypertension. Secondly, there is evidence that vasopressin is synthesized not only in the hypophysial-pituitary axis but also in peripheral tissues including the heart where it acts as a paracrine hormone. Thirdly, vasopressin has vasoconstrictor, mitogenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…The antagonism of V 2 receptors induces the elimination of free-water (''aquaresis'') without depleting electrolytes or activating neurohormonal systems, common side effects of diuretic therapy [51]. Furthermore, the antagonism of V 1A /V 2 receptors provides aquaresis induced by the V 2 receptor stimulation and should suppress the deleterious cardiac effects caused by the activation of the V 1A receptor [49,52]. Experimental models and clinical trials have shown that AVP receptor antagonists represent a promising approach for the treatment of hyponatremia in HF [53,54].…”
Section: Treatment and Avp Antagonismmentioning
confidence: 98%
“…The antagonism of V 2 receptors induces the elimination of free-water (''aquaresis'') without depleting electrolytes or activating neurohormonal systems, common side effects of diuretic therapy [51]. Furthermore, the antagonism of V 1A /V 2 receptors provides aquaresis induced by the V 2 receptor stimulation and should suppress the deleterious cardiac effects caused by the activation of the V 1A receptor [49,52]. Experimental models and clinical trials have shown that AVP receptor antagonists represent a promising approach for the treatment of hyponatremia in HF [53,54].…”
Section: Treatment and Avp Antagonismmentioning
confidence: 98%
“…The use of an AVP receptor antagonist to treat hyponatremia has other advantages over existing therapies. In patients with CHF, AVP antagonism has the potential to produce effective and sustained reductions in congestion without worsening renal function, potassium depletion, or hypotension that may be associated with diuretics [67]. In low-output CHF, V 2 receptor antagonists can correct the associated conditions of hyponatremia, hypo-osmolality, and water retention [54].…”
Section: Avp Receptor Antagonismmentioning
confidence: 99%
“…A V 1A /V 2 receptor antagonist provides V 2 -mediated renal aquaresis and may suppress the negative hemodynamic and cardiac effects caused by activation of the V 1A receptor [34, 67]. Conivaptan (YM-087) is currently the only agent in this class [77] and has recently been approved by FDA.…”
Section: V1a/v2 Receptor Antagonistmentioning
confidence: 99%
“…32 The clinical significance of V 1A receptor antagonism remains to be elucidated, but this approach might suppress the negative hemodynamic and cardiac effects caused by V 1A -mediated vasoconstriction. 40,41 In addition, studies in animal models of subarachnoid hemorrhage and embolic stroke suggest that V 1A receptor antagonism protects against cerebral vasospasm and neurological deficits associated with ischemic brain injury.…”
Section: Avp Receptor Antagonists: a New Approach To The Treatment Ofmentioning
confidence: 98%